Personality Traits and Entrepreneurial Intentions: Financial Risk-Taking as Mediator - Salameh, Anas A.; Akhtar, Hameeda; Gul, Rani; Omar, Abdullah Bin; Hanif, Sobia (Frontiers in Psychology, 2022)
The interaction between environment and individual personality determines career. Over the past decades, the role of personality traits in explaining entrepreneurship cannot get much attention of researchers. To fill this gap, this study aims to investigate the effect of personality traits (extraversion, openness to experience, conscientiousness, neuroticism, and agreeableness) on the entrepreneurial intentions (EI) along with the mediating role of financial risk taking (FRT). Sample size consists of 500 students of business and management of different universities of Pakistan, out of which 466 useable questionnaires were collected and analyzed. The results of the study are consistent with conventional wisdom as explored by past studies. In line with past studies and proposed hypothesis, we found that both extraversion and openness to experience have a positive association with FRT, whereas neuroticism, conscientiousness, and agreeableness have negative association with FRT. The results also revealed that there is positive association between FRT and EI; however, FRT did not mediate the relationship between agreeableness and EI.